Cryosurgery of breast cancer - Niu, Lizhi (AME Publishing Company, 2012)
With recent improvements in breast imaging, the ability to identify small breast tumors is markedly improved, prompting significant interest in the use of cryoablation without surgical excision to treat early-stage breast cancer. The cryoablation is often performed using ultrasound-guided tabletop argon-gas-based cryoablation system with a double freeze/thaw cycle. Recent studies have demonstrated that, as a primary therapy for small breast cancer, cryoablation is safe and effective with durable results, and can successfully destroy all cancers <1.0 cm and tumors between 1.0 and 1.5 cm without a significant ductal carcinoma-in-situ (DCIS) component. Presence of noncalcified DCIS is the cause of most cryoablation failures. At this time, cryoablation should be limited to patients with invasive ductal carcinoma <1.5 cm and with <25% DCIS in the core biopsy. For unresectable advanced breast cancer, cryoablation is a palliation modality and may be used as complementary for subsequent resection or other therapies.